Analisis Kerapatan dan Ukuran Stomata Tumbuhan Dikotil pada Area Naungan dan Terbuka di Arboretum Sempaja (sebagai Bahan Ajar Materi Jaringan Tumbuhan Kelas XI SMA) - Nuryani, Nuryani; Herliani, Herliani; Purwati, Sri; Akhmad, Akhmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Shading causes differences in light intensity that trigger physiological and morphological variations in leaves, including stomata density and size as a form of adaptation to balance photosynthesis and transpiration. This phenomenon is the basis for selecting the research, because it illustrates the adaptive ability of plants to changes in the microenvironment in their natural habitat. This study aims to analyze the density and size of stomata of dicotyledonous plants growing in shaded and open areas in the Sempaja Arboretum. This study uses a descriptive quantitative approach with samples of several dicotyledonous plant species growing in shaded and open areas. Data were obtained through microscopic observation of leaf epidermis preparations using direct section techniques, optilab, and image raster 3. Statistical analysis showed that the density of stomata in open areas was higher (480 stomata/mm²) than in shaded areas (323 stomata/mm²). However, the size of the stomata did not show a consistent pattern; The average length (25.21 µm) and width (18.45 µm) of stomata in the shaded area were slightly larger than those in the open area (24.16 µm and 17.18 µm). These results indicate that high light intensity encourages increased stomatal density as an adaptive mechanism to support photosynthesis.